The Links Between Social Motivational Engagements, Brand Community Commitment and Repurchase Intention Across Online Brand Communities - Časas, Ramūnas; Palaima, Tomas; Mironidze, Lasha (Organizations and Markets in Emerging Economies, 2019)
The study focuses on the relationships between social motivational engagements, brand community commitment and repurchase intentions across marketer-generated and customer-generated online brand communities. The current study demonstrates that online brand community commitment mediates the effects of all the six motivational engagements (self-expression, connecting, helping, like-minded discussions, seeking assistance, and validation) on repurchase intention. The type of online brand community does not moderate any relationships between social motivational engagements and brand community commitment as expected. However, the current study demonstrates that the moderator affects the link between brand community commitment and repurchase intention indicating moderated mediation. In other words, the relationship between the two constructs becomes stronger in the marketer-generated online brand community. Consequently, the type of online brand community affects the links between the six social motivations and repurchase intention. Specifically, the effects of the six motivations on repurchase intention become stronger in the marketer-generated online community.
Keywords: brand community; social motivational engagements; brand community commitment; repurchase intention